2( 13X + 6
23 ( 13X + 6)
23 ( 13X + 6)2
13 ( 13X + 6)2
Correct answer is B
Y = ( 13X + 6)2
dydx = 2( 13X + 6) 13
= 23 ( 13X + 6)
If t varies inversely as the cube of s, and t = 24, when s = 3, find t when s = 2 ...
In the diagram above, ∠PTQ = ∠URP = 25° and XPU = 4URP. Calculate ∠USQ. ...
If y varies directly as the square root of x and y = 3 when x&nbs...
A wire was shaped to form a square of area 81cm2. An equilateral triangle was formed by the sam...
Simplify (0.09)2 and give your answer correct to 4 significant figures...
Find the 8th term of the A.P -3, -1, 1 ...... ...
Solve for t in the equation 34t + 13(21 - t) = 11...
If b = a + cp and r = ab + 12cp2, express b2 in terms of a, c, r....